Hipertensi dan Komplikasi Yang Menyertai Hipertensi - Farid Husaini; Tischa Rahayu Fonna (Jurnal Medika Nusantara, 2024)
Hypertension is a condition in which the blood pressure in the systemic arteries remains consistently high. Blood pressure is generally measured as the result of systolic blood pressure (pressure when the heart contracts and delivers blood to the arteries) and diastolic blood pressure (pressure when the heart relaxes). The threshold for diagnosing hypertension varies depending on the measurement method used. Hypertension is often referred to as the "silent killer" because it generally does not produce symptoms until serious complications develop. Some complications associated with hypertension later in life are related to cardiovascular disease, Chronic Kidney Disease, and cognitive disorders. Effective prevention is carried out to reduce the burden of disease and accompanying complications later in life.